Characterization of a bacteriophage from urban sewage obtained with the bacterium Staphylococcus aureus (Stamford Journal of Microbiology, 2020)
Bacteriophages are viruses of bacteria that have received significant attention in the last decades due to their potential as an alternative to the antibiotics, as well as their applicability in the selective control of bacterial species harmful to food. In this context, this work reports the partial results of a viral filtrate named P4CSa that was obtained with the bacterium Staphylococcus aureusand characterized by the viral host range and the restriction fragment length polymorphism technique. The results indicate that the phage P4CSa probably belongs to the order Caudovirales, it presents a polyvalent host range, and it can be preserved for the long term in the form of filtrated lysates stored at 4°C, suggesting that the phage P4CSa may have the potential for the development of a pharmaceutical product indicated for the biocontrol of pathogenic bacteria.Stamford Journal of Microbiology, Vol.10 (1) 2020: 20-24